PEMANFAATAN ACTIVE PRESENTER SEBAGAI TEKNOLOGI PEMBELAJARAN PADA PROGRAM STUDI PENDIDIKAN MATEMATIKA FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUMATERA UTARA - Rahmaini Rahmaini; Nanda Novita (AXIOM : Jurnal Pendidikan dan Matematika, 2018)
The development of technology is moving quickly and widely utilizedin manyareaon everyday life. Today, the used of technology ineducation. In this research, learning computer animation on students offaculty of Tarbiyah and Pedagogy UIN North Sumatera, as Teaching inthe Educational of Arabic language and mathematics education. Thefunction of system innovation animation to utilization for learningmaterials.